Rhaphium Meigen (Diptera, Dolichopodidae) from the Taimyr Peninsula (Russia), with description of a new species - Negrobov, Oleg P.; Barkalov Аnatolii V.; Selivanova Оlga В. (Zootaxa, 2012)
Eight species of Rhaphium Mg. are recorded from the southern tundra of the Taimyr Peninsula (Russia), including the description of a new species, Rhaphium borisovi Negrobov, Barkalov & Selivanova sp. nov. The new species is similar to Rhaphium gruniniani Negrobov and differs from it by yellow fore coxa, equal length of hind tarsomeres 1–2 and broader inner lobe of cercus. The female of Rhaphium beringiense Negrobov & Vockeroth is described. A key to Siberian species (exclusive of Far East species) of the genus Rhaphium is presented and morphological characters of all species are illustrated.